Implementation of the 5T Principle in Oil Palm Fertilization - Raihan Aditiya; Budi Winarni; Andi Lelanovita Sardianti; Rossy Mirasari; Humairo Aziza (Politeknik Pertanian Negeri Samarinda, 2026)
Fertilization constitutes a crucial maintenance practice in enhancing the growth and productivity of oil palm plantations. The effectiveness of fertilization management is strongly affected by the implementation of the 5T principle, which includes the appropriate type, dosage, timing, application method, and placement. This research was conducted to identify the implementation of the 5T principle in fertilization activities for mature oil palm plants (TM) and to assess its conformity with the company’s Annual Work Plan (RKT) and Standard Operating Procedures (SOP). The study employed a descriptive qualitative approach using a case study method at Afdeling II Feliza Estate of PT Cahaya Anugerah Plantation. Research data were collected through direct field observations, interviews with fertilization foremen and workers, as well as documentation review consisting of SOPs, RKTs, and Foreman Workbooks (BKM). The sampling technique was carried out purposively in four plantation blocks, namely I002, I012, 1013, and K015. Data analysis involved several stages, including data collection, data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of the 5T principle in fertilization activities had generally followed the company’s operational procedures. The indicators related to appropriate dosage, timing, and placement were implemented according to the established standards. However, discrepancies were still identified in the appropriate type and application method, particularly in terraced areas where the pocket method was recommended, yet the broadcasting system continued to be practiced.